2007
DOI: 10.1038/sj.emboj.7601766
|View full text |Cite
|
Sign up to set email alerts
|

Replication blocking lesions present a unique substrate for homologous recombination

Abstract: Homologous recombination (HR) plays a critical role in the restart of blocked replication forks, but how this is achieved remains poorly understood. We show that mutants in the single Rad51 paralog in Caenorhabditis elegans, rfs-1, permit discrimination between HR substrates generated at DNA double-strand breaks (DSBs), or following replication fork collapse from HR substrates assembled at replication fork barriers (RFBs). Unexpectedly, RFS-1 is dispensable for RAD-51 recruitment to meiotic and ionizing radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
103
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 67 publications
11
103
0
Order By: Relevance
“…This group contains the human proteins rad51B, rad51C, rad51D, XRCC2, and XRCC3, which form two known complexes that are implicated in DNA damage repair. Rfs-1 appears most similar to Rad51D (Ward et al 2007). Thus, rfs-1 appeared to be a likely candidate to be the gene responsible for the Him phenotype.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…This group contains the human proteins rad51B, rad51C, rad51D, XRCC2, and XRCC3, which form two known complexes that are implicated in DNA damage repair. Rfs-1 appears most similar to Rad51D (Ward et al 2007). Thus, rfs-1 appeared to be a likely candidate to be the gene responsible for the Him phenotype.…”
Section: Resultsmentioning
confidence: 71%
“…One of these deletions, eDf25, originally known as unc-86(e1416), removes part of the unc-86 promoter and an upstream operon with three genes ( Figure 1A). The first two genes in the operon are uncharacterized; the third gene, rfs-1, is the only member of the Rad-51 paralog group found in C. elegans (Ward et al 2007). This group contains the human proteins rad51B, rad51C, rad51D, XRCC2, and XRCC3, which form two known complexes that are implicated in DNA damage repair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to findings in G1 cells, which lack the opportunity for recombinational repair (14), in the G2 cells we found efficient loss of SMD at later times, restitution of chromosomes, the disappearance of MBN-sensitive sites, and high survival rates, all of which required Rad52 and Rad51. Although recombination repair can restore collapsed replication forks (45,46), there is little direct evidence that HR directly processes and repairs replication-blocking lesions located on ssDNA. Using a plasmid-based assay, Adar et al (47) showed that gaps opposite an abasic site or a benzo[a]pyrene-guanine adduct could be repaired by HR in mammalian cells.…”
Section: Compromised Tls Activity Leads To Increased Recombinant Molementioning
confidence: 99%